2021
DOI: 10.52711/0974-360x.2021.00660
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Aluminium on Female Reproductive System in Presence of Ethanol Coexposure

Abstract: Both aluminium and ethanol are pro-oxidants and toxic. Uncontrolled use of aluminium and increasing trends of ethanol consumption in India increased the chance of coexposure to aluminium and ethanol. There are possibilities, that both of them follow common mechanisms to produce reproductive toxicity. The present study was planned to identify the effects of aluminium administration on the microscopic structure of ovary and to clarify any possible protection conferred by the concomitant administration of ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…5,39,40 Our study is in agreement with the previous report by demonstrating a diminution in antioxidant enzymes, an increase in inflammatory biomarkers and LPO following EtOH exposure. Alteration in the histo-architecture due to EtOH exposure in the testicular microenvironment was earlier reported 41 due to OS, LPO and inflammation. Histological results in the present study indicated that EtOH exposure elicited moderate degeneration of the Sertoli cells and the necrotic appearance of the Leydig cells.…”
Section: Discussionmentioning
confidence: 63%
“…5,39,40 Our study is in agreement with the previous report by demonstrating a diminution in antioxidant enzymes, an increase in inflammatory biomarkers and LPO following EtOH exposure. Alteration in the histo-architecture due to EtOH exposure in the testicular microenvironment was earlier reported 41 due to OS, LPO and inflammation. Histological results in the present study indicated that EtOH exposure elicited moderate degeneration of the Sertoli cells and the necrotic appearance of the Leydig cells.…”
Section: Discussionmentioning
confidence: 63%
“…Hence, ethanol-induced elevation of germ cell apoptosis and necrosis and suppression of cell proliferation may contribute to testicular atrophy. 28 These effects were observed in the reduced tubular diameter and cross-sectional areas of the treated animals. However, when the animals were co-exposed to both ethanol and aluminium, the vacuolar-degenerative changes appeared in the cytoplasm of the spermatogenic epithelium and in the sertoli cells and abnormal distribution of spermatozoa in the Lumina.…”
Section: Discussionmentioning
confidence: 96%
“…According to the study, there was a lack of normal spermatogenic cell distribution in the seminiferous tubules, and some spermatocytes were fragmented in the lumen. The use of combined treatment of ethanol and aluminum via the oral route caused vascular degenerative alterations in the cytoplasm of spermatogenic epithelium and Sertoli cells in testes (Ghosh et al, 2021a).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Exposure to pro-oxidants and toxic chemicals, such as aluminum, can enhance alcohol toxicity (Ghosh et al, 2021a). The microscopic structure of the testes was identified using a three-month-experimental study with 16 male rats, including three treatments and one control group.…”
Section: Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation